Heroes and poets. Literary influences on "Héroes del Silencio" discography - Pascual Auqué, Patricia (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The relationship between music and literature is a constant since the beginning of both with song being, clearly, the genre where this relationship is most evident. Literature has influenced music decisively, in the same way the latter has served as inspiration for literati. In this article we seek to show literary influences present at «Héroes del Silencio» musical output, especially those coming from symbolist poetry. Verse handling, artist's standpoint on society or praising of the mundane pleasures are part of the legacy in this poetry that makes itself apparent by listening songs from the aragonese band.
Keywords: Héroes del Silencio; poetry; symbolism; Comparative Literature; literary influences